Cu-CHA material efficient in the SCR process in the presence of water and CO2 - Cortés-Reyes, Marina; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; Alemany-Arrebola, Luis José (My University, 2017)
A reproducible method for the synthesis of SCR active Cu-CHA materials has been developed, which allows the incorporation of up to 4% of copper inside the cavities of the zeolite. These materials are highly efficient in the removal of NOx by reaction with ammonia, even in the presence of water and CO2 in the reaction atmosphere. Cu2+ species are the active species in the reaction and in contact with water and CO2, the hydrated-carbonate Cu2+ species placed in the 8-rings were identified as the responsible for the improvement in the activity.
Keywords: Descontaminación; SCR; quasi real condition; Cu-CHA